Análisis y simulación a través de un modelo matemático para reducir el efecto handover ping-pong en una red 4g - Escudero Padilla, Karina Pilar (2021)
This research addressed the topic of handover analysis and simulation to reduce the ping- pong handover effect in a 4G network through the development of a mathematical model. In a 4G network, a significant problem is the mobility of the user who is connected to the network through a base station (eNB), which is placed in a scenario composed of what is known as a cluster or cells, since when the power that reaches the transmitting base station at point A (eNbPtx-A), which is the edge of the cell, it is necessary to do a handover, what is known as handover (HO), this process is carried out when the source node is disconnected first and In a short time it establishes a new communication link with the destination node (eNbPtx-B) so that when a user has little mobility between coverage areas, it causes the HO ping-pong effect that occurs when transferring from one cell to another but it quickly returns to the original cell, wasting signaling resources, and interrupts communication, generating a significant impact on the quality of service. The objective of this research is to analyze the handover or handover process in a 4G network by adapting a mathematical model, which will be applied in the simulation of the network in order to reduce the ping-pong handover effect. In this work, it is proposed to improve the network for which significant data from a handover was used, which are the firing time (TTT) and its hystéresis (HOM) as a function of the signal-noise- interference ratio (SINR). performed using an algorithm obtained from the mathematical model, since the result tables show that the handover failure rate and ping-pong handover failures are significantly reduced.